TELAAH ULANG KEWAJIBAN ZAKAT PADI DAN BIAYA PERTANIAN SEBAGAI PENGURANG ZAKAT (Analisis ‘’Fatwa - Fatwa” di Media Sosial) - M, suhadi (UIN Sunan Kudus, 2014)
The Government of Indonesia as ulil amri need to provide practical guidanceand technical guidelines that detail related about zakat agriculture because ofthe law of zakat has not been set out clearly and forcefully about the alms ofrice although it can be argued, but would be stronger if the alms of rice set outin black and white. Even if necessary can also be a radical government did notimpose the obligation of zakat rice because fiqh in the comparison schools it islegitimized by salafi circles and schools Adhahiri that salahstaunya of the highpriest of the famous Ibn Hazm their knowledge in the field of Islamic law.